2019
DOI: 10.1111/tme.12581
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers and community perceptions of blood transfusion for children with severe anaemia in Uganda

Abstract: SUMMARY Objective To describe local perceptions of blood transfusion for children with severe anaemia in Uganda. Background Blood transfusion is a common emergency treatment for children with severe anaemia and saves millions of lives of African children. However, the perceptions of transfusion recipients have not been well studied. A better understanding of the perceived risk may improve transfusion care. Methods A qualitative study based on 16 in‐depth interviews of caregivers of transfused children, and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[25][26][27] Lower percentages of 88.3% and 75.5% were however, reported in Ethiopia. [8,23] In addition, a qualitative study based on in depth interviews of caregivers of transfused children and focus group discussions with community members in Uganda [28] documented that care-givers of children and community members held blood transfusion in high regard and it was being valued as a life-saving procedure. More than 2/3 rd (70.6%) participants knew at least one indication of blood transfusion in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Lower percentages of 88.3% and 75.5% were however, reported in Ethiopia. [8,23] In addition, a qualitative study based on in depth interviews of caregivers of transfused children and focus group discussions with community members in Uganda [28] documented that care-givers of children and community members held blood transfusion in high regard and it was being valued as a life-saving procedure. More than 2/3 rd (70.6%) participants knew at least one indication of blood transfusion in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There was widespread perceived risk of blood transfusion including risk of HIV infection and blood incompatibilities among caregivers of children and community members in a qualitative study carried out in Uganda. [28] Interestingly, a cross-sectional descriptive study of health workers in the University of Benin Teaching Hospital, [29] Nigeria showed that almost all the participants (95.7%) were aware of the risk of infection through blood transfusion.…”
Section: Discussionmentioning
confidence: 99%